2017
DOI: 10.3389/fphar.2017.00191
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Analysis of the Anti-epileptic Mechanisms of Fenfluramine in scn1a Mutant Zebrafish

Abstract: Dravet syndrome (DS) is a genetic encephalopathy that is characterized by severe seizures and prominent co-morbidities (e.g., physical, intellectual disabilities). More than 85% of the DS patients carry an SCN1A mutation (sodium channel, voltage gated, type I alpha subunit). Although numerous anti-epileptic drugs have entered the market since 1990, these drugs often fail to adequately control seizures in DS patients. Nonetheless, current clinical data shows significant seizure reduction in DS patients treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
169
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 110 publications
(176 citation statements)
references
References 56 publications
4
169
1
2
Order By: Relevance
“…49 Deletion of central serotonergic neurons resulted in reduced arousal and deficits in respiratory responses to elevated CO 2 levels in transgenic rodents. [22][23][24][25][26]52,53 Recent autopsy findings in human SUDEP cases also show serotonergic abnormalities in brainstem nuclei, including the raphe nuclei. 10,51 Dietary supplementation with 5-hydroxytryptophan, a precursor of serotonin synthesis, significantly reduced the incidence of Sz behaviors and blocked S-IRA in DBA/1 mice.…”
Section: Discussionmentioning
confidence: 98%
“…49 Deletion of central serotonergic neurons resulted in reduced arousal and deficits in respiratory responses to elevated CO 2 levels in transgenic rodents. [22][23][24][25][26]52,53 Recent autopsy findings in human SUDEP cases also show serotonergic abnormalities in brainstem nuclei, including the raphe nuclei. 10,51 Dietary supplementation with 5-hydroxytryptophan, a precursor of serotonin synthesis, significantly reduced the incidence of Sz behaviors and blocked S-IRA in DBA/1 mice.…”
Section: Discussionmentioning
confidence: 98%
“…With a view to repurpose marketed drugs for the treatment of DS, we sought to interrogate compounds using the zebrafish scn1Lab −/− mutant platform . We previously demonstrated that the modulation of some 5‐HT subtype receptors (ie, 5‐HT 2A , 5‐HT 2C , and 5‐HT 1D ) can effectively reduce seizures in the scn1Lab −/− mutant model . Here, we test three marketed compounds (ie RIZA, LIS, and EFA) that are known to have a clear on‐ or off‐target 5‐HT profile.…”
Section: Discussionmentioning
confidence: 99%
“…All procedures were carried out following the Declaration of Helsinki and according to the European Community Council directives 86/609/EEC. Husbandry and genotyping ( scn1Lab mutants) of zebrafish was performed as described previously . Wild‐type zebrafish (AB strain) were used for experiments with PTZ and EKP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations